Public places: the retail-oriented public realm in Beijing - Su, Guangzi (2012)
With the increasing development of economy and society in China, uses of public urban places have been changed by an incredible pace, especially in Beijing, the capital of China. The public space in local urban environment plays a significant role for catering to people's functional, social and leisure needs. The focus of this research is to explore the relationship between the retail-oriented public places and people's use within three selected study sites in Beijing, Wangfujing Street, Sanlitun Village, and The Place, and to examine the retail public spaces which can satisfy the physical and psychological needs of people when they take activity in such places. Through literature review to analyse the theoretical issues on different factors, such as culture, urban design, physical setting, historical context, and contemporary use, and especially the retail public places developed in Chinese context, etc. and to establish the awareness of what the research subject refer to and what such places people like to use. And then focus on the public life in the city of Beijing in practice with the aim of finding out how these retail-oriented public places are understood, managed and used, including the use and quality of design amenities for sitting, circulation, and related activities by local people in urban environment. To address this research, a qualitative research methodology is adopted mainly involves observation, interview, and small number of questionnaire. The mixed-methods approach is undertaken by using behaviour mapping and user perception to understand the public environment as a combination of patterns of behaviour and patterns of the physical environment.